Estudio de los Corresponsales No Bancarios y su efecto en la inclusión financiera en la ciudad de Loja - Sánchez Malla, Dayanna Stefania (2022)
The purpose of this degree work is to study the Non-Banking Correspondents and thus determine the level of acceptance they have in the city of Loja, for this 383 surveys were applied to the population of Loja between 20 and 74 years of age, in order to obtain information related to the topic of study. Once the information was collected, statistical tools such as Microsoft Excel 2019 and IBM SPSS Statistics 21 were used to process the data, obtaining that 67% of the citizens expressed their acceptance of the CNBs, indicating that they have become the main alternative for accessing different financial services. However, despite the fact that the CNBs have a high level of acceptance, there are aspects that need to be improved so that these financial intermediation channels can offer quality services to users.